2021
DOI: 10.1039/d0fo02274h
|View full text |Cite
|
Sign up to set email alerts
|

Maternal organic selenium supplementation during gestation improves the antioxidant capacity and reduces the inflammation level in the intestine of offspring through the NF-κB and ERK/Beclin-1 pathways

Abstract: Selenium (Se) is postulated to protect against inflammation in the gut by attenuating oxidative stress. This study was conducted to investigate the effects of maternal 2-hydroxy-4-methylselenobutanoic acid (HMSeBA), an organic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Nelson et al [ 61 ] stated that Se supplementation was able to induce the polarization of bone marrow-derived macrophages from M1 macrophages towards M2 macrophages. Several studies have shown that OH-SeMet supplementation in non-stressed conditions is capable of decreasing the production of proinflammatory cytokines such as IL-1β or TNFα and increase the expression of anti-inflammatory cytokines such as IL-10 [ 24 , 37 , 62 , 63 , 64 ]. Nevertheless, contrary to NAC, when a challenge was induced, OH-SeMet supplementation helped the macrophages to control the cytokine production by decreasing both proinflammatory cytokines (TNFα and IL-1β) and maintaining the anti-inflammatory cytokine IL-10, as previously described in other tissues [ 27 , 37 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson et al [ 61 ] stated that Se supplementation was able to induce the polarization of bone marrow-derived macrophages from M1 macrophages towards M2 macrophages. Several studies have shown that OH-SeMet supplementation in non-stressed conditions is capable of decreasing the production of proinflammatory cytokines such as IL-1β or TNFα and increase the expression of anti-inflammatory cytokines such as IL-10 [ 24 , 37 , 62 , 63 , 64 ]. Nevertheless, contrary to NAC, when a challenge was induced, OH-SeMet supplementation helped the macrophages to control the cytokine production by decreasing both proinflammatory cytokines (TNFα and IL-1β) and maintaining the anti-inflammatory cytokine IL-10, as previously described in other tissues [ 27 , 37 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that OH-SeMet supplementation in non-stressed conditions is capable of decreasing the production of proinflammatory cytokines such as IL-1β or TNFα and increase the expression of anti-inflammatory cytokines such as IL-10 [ 24 , 37 , 62 , 63 , 64 ]. Nevertheless, contrary to NAC, when a challenge was induced, OH-SeMet supplementation helped the macrophages to control the cytokine production by decreasing both proinflammatory cytokines (TNFα and IL-1β) and maintaining the anti-inflammatory cytokine IL-10, as previously described in other tissues [ 27 , 37 , 64 ]. It is important to remark that the control of IL-10 production is needed in stressed conditions since it is described that high IL-10 production leads to a suppression of the immune response and, therefore, a failure to control the infection [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activities of glutathione peroxidase (GPX), glutathione reductase (GR), thioredoxin reductase (TXNRD), total antioxidative capability (T-AOC), total superoxide dismutase (T-SOD) and malondialdehyde (MDA) of gilts' serum, liver, ovary, and supernatant and GCs of in vitro experiment were quantified by the respective assay kits (Nanjing Jiancheng Institute, Jiangsu, China). Briefly, the activities of GPX, GR and SOD were assayed as described by Mou et al ( 19 ). MDA content was measured based on the thiobarbituric acid (TBA) method.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have confirmed that Se can regulate the immune response of DCs in chickens, mice, and humans [ 49 , 65 , 66 , 67 ]. Potential mechanisms by which Se is involved in the regulation of immune cell function include reactive oxygen species production and species, calcium and redox signaling, extracellular signal-regulated kinase (ERK), hypoxia-inducible factor 1α (HIF-1α), and NF-κB pathways [ 67 , 68 , 69 , 70 , 71 , 72 ]. A recent study in mice demonstrated that low and high Se affect the secretion of cytokines and impair immune function in the spleen [ 73 ].…”
Section: The Role Of Selenoproteins In the Prevention Of Food Allergiesmentioning
confidence: 99%